Clinical efficacy and safety of icaritin in patients with hepatocellular carcinoma: a real-world study - He, Jingchang; Zhuang, Lanlan; Lei, Yi; Wang, Biao; Chen, Huaiyu; Kang, Shuai; Liu, Dingli; Wang, Kunyuan; Yu, Wenxuan; Lu, Yuchen; Cheng, Yang; Zhu, Yun (Frontiers in Pharmacology, 2026)
BackgroundIcaritin, a natural compound extracted from Epimedium, has demonstrated efficacy and a favorable safety profile in treating hepatocellular carcinoma (HCC), providing an option for patients intolerant to conventional treatment. However, real-world data remain limited. To assess the therapeutic potential and safety of icaritin for patients with unresectable HCC (uHCC), we conducted a retrospective analysis at our center.MethodsThis study analyzed 26 HCC patients treated with icaritin-based regimens (monotherapy, n = 10; combination therapy, n = 16) at Nanfang Hospital (June 2018–June 2024). We evaluated efficacy outcomes, including objective response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS), as well as safety and health-related quality of life (HRQOL).ResultsThe monotherapy group showed a DCR of 60.0%, median PFS of 3.5 months, and a median OS of 9.4 months. The combination therapy group had a DCR of 93.8%, a median PFS of 5.7 months, and a median OS of 10.6 months. The incidence of Grade 3 treatment-related adverse events (TRAEs) was 13.9%, and no Grade 4+ TRAEs were observed. HRQOL was maintained throughout treatment in either group. One patient with BCLC stage C achieved a partial response after 2 months of icaritin monotherapy and a complete response after 8 months, with PFS exceeding 18 months.ConclusionIcaritin-based therapy has certain efficacy and a favorable safety in uHCC, suggesting a therapeutic alternative for uHCC patients ineligible for standard treatments.